Small millets are a good source for nutritional and food security - Yadav, Rashmi; Yadav, V K; Pragya, Pragya; Dutta, M. (Indian Farming, 2015)
Small millets, though less known and less explored crop holds a very high nutritional status. They are far superior to the cereals since they have a better nutritional profile in terms of minerals, calcium, iron and manganese. The grains of barnyard millet contain high amount of protein, carbohydrates, crude fibre and non-starchy polysachharides. Various forms of products, (eatables) are prepared and sold in the market and many preparations of these millets are known to be made by the economically weaker section of the people. More awareness about the nutritional richness of the small millets need to be made among people for adopting small millets in their daily diet.